Fertility Preservation in Female Patients with Cancer. Issue 8 (August 2022) - Mahmood, S.; Drakeley, A.; Homburg, R.; Bambang, K.
Abstract: Advances in cancer treatment with resultant dramatic improvements in long-term survival have led to increasing awareness of the wide range of medical and social issues faced by survivors of malignancy. The potential deleterious effects on fertility are a significant worry of women and trans gender men, and the rising trend in delaying childbearing and the higher proportion of patients who have not completed their family at the time of diagnosis increases the demand for an optimised fertility-preservation service. Fertility preservation for this group following a diagnosis of cancer is a rapidly expanding area of reproductive medicine, although provision for such treatment often varies by region. In the past, there were few treatment options, but with dramatic improvements in oocyte cryopreservation and, more recently, ovarian tissue cryopreservation, this area of fertility care has broadened substantially. This review will be exploring areas that apply to all cisgender women, but not necessarily all trans men and non-binary individuals. There are specific considerations in fertility preservation for trans people, which are beyond the scope of this paper. All individuals with female reproductive organs should be offered the opportunity to discuss fertility preservation prior to starting potential gonadotoxic treatment. Failure to do this may negatively influence their anticancer treatment choices and adherence to treatment regimens. There are currently few networks streamlined around offering this service and as demand for these treatment options increases, it is recognised that these complex patients require specialist management within recognised care pathways. Here we are looking to describe some of the unique challenges associated with providing a state-of-the-art service, particularly in a financially unpredictable climate in the midst of the COVID-19 pandemic. Highlights: The potential deleterious effects of cancer treatment on fertility are a significant worry of and this increases the demand for an optimised fertility-preservation service. A service that engages patients and provides them with suitable guidance to aid their decision-making is needed. Regional fertility preservation networks, in conjunction with reproductive and oncology teams would help with this. Post-covid medicine is a rapidly changing landscape for a group of patients who already have a large burden, making long-term predictions impossible to assess.